Penguatan Kapasitas Petani rakyat melalui Sosialisasi Penyerapan Garam Rakyat Tahun 2025 di Kabupaten Bangkalan - Dewabrata, Bondan; Ahmadi, Raden Khaeru; Sa’adah, Siti; Jasuli, Akis; Fabri, R. Raditya Wira; Syakina, Annisa; Rahardjo, Rosnindar Prio Eko; Haqiqi, R.Nurfi Qolbi; Rahman, Taufikur; Ludianto, Ludianto; Ismail, Jamal (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
Bangkalan Regency is one of the strategic salt-producing regions on Madura Island, with great potential to support national salt resilience. However, salt farmers in this area still face several serious challenges, such as low product quality, limited access to sustainable markets, and weak institutional support for salt farmers. To address these issues, this community service activity was carried out with the main objective of strengthening the capacity of salt farmers through a socialization program on the absorption of local salt. A participatory approach was employed, with the stages of activity including: identifying partner needs, preparing educational materials tailored to local contexts, conducting interactive discussions, and evaluating the impact using pre- and post-activity questionnaires. The socialization program was held in early 2025 in Klampis District, one of the salt production centers in Bangkalan. A total of 20 local salt farmers, consisting of 18 men and 2 women aged between 35–55 years, participated in the activity. The materials presented covered the mechanisms of salt absorption by cooperatives, industrial quality standards, and clean production technologies such as the use of geomembrane liners and closed crystallization systems. Based on the evaluation results, there was a significant increase in participants’ knowledge, supported by high satisfaction scores regarding the quality of the materials and the delivery methods used by the presenters. Participants also showed strong enthusiasm during the discussions. This activity proved effective in enhancing the technical and institutional awareness of salt farmers and encouraging them to adopt more modern, efficient, and market-oriented production systems. It also helped foster a spirit of collaboration toward the self-sufficiency of the local salt industry.ABSTRAKKabupaten Bangkalan merupakan salah satu wilayah strategis penghasil garam rakyat di Pulau Madura yang memiliki potensi besar dalam mendukung ketahanan garam nasional. Namun demikian, para petambak di wilayah ini masih menghadapi sejumlah tantangan serius, seperti rendahnya mutu hasil produksi, terbatasnya akses pasar yang berkelanjutan, serta lemahnya kelembagaan petani garam. Untuk menjawab persoalan tersebut, kegiatan Pengabdian kepada Masyarakat ini dilaksanakan dengan tujuan utama memperkuat kapasitas para petambak melalui sosialisasi penyerapan garam rakyat. Pendekatan yang digunakan bersifat partisipatif, dengan tahapan kegiatan meliputi: identifikasi kebutuhan mitra, penyusunan materi sosialisasi sesuai kebutuhan lokal, pelaksanaan diskusi interaktif, serta evaluasi berbasis kuesioner sebelum dan sesudah kegiatan. Sosialisasi ini dilaksanakan pada awal tahun 2025 di Kecamatan Klampis, salah satu sentra produksi garam di Bangkalan. Sebanyak 20 petambak rakyat, terdiri dari 18 laki-laki dan 2 perempuan dengan rentang usia 35–55 tahun, menjadi peserta kegiatan. Materi yang disampaikan mencakup mekanisme penyerapan garam oleh koperasi, standar mutu industri, serta teknologi produksi bersih seperti penggunaan geomembran dan sistem kristalisasi tertutup. Berdasarkan hasil evaluasi, terdapat peningkatan signifikan dalam pengetahuan peserta, didukung oleh skor kepuasan peserta yang tinggi terhadap kualitas materi dan metode penyampaian narasumber. Antusiasme peserta juga terlihat selama diskusi berlangsung. Kegiatan ini terbukti efektif dalam meningkatkan kesadaran teknis dan kelembagaan petani, serta mendorong mereka untuk menerapkan sistem produksi yang lebih modern, efisien, dan berorientasi pasar. Kegiatan ini juga memperkuat semangat kolaboratif menuju kemandirian industri garam rakyat.